THE RECODIFICATION OF LABOUR LAW IN LITHUANIA 2016–2017 - Davulis, Tomas (Teisė, 2017)
The article aims to reveal qualitatively the new features of legal regulation of labour relations, which in the near future will affect the legal status of employees in Lithuania and the competitiveness of the country‘s labour market. The article examines and analyses the reasons of the recodification of Lithuanian labour law and the process of creation of the new Labour Code. Through comparative, systematic and other methods the provisions of the new Labour Code of Lithuania are examined in accordance with the general characteristics of the code as a legal act and according to what goals the recoding initiators themselves have raised and how it was implemented in the text of the law.